2022
DOI: 10.3390/ijerph20010368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on CSR Activities of Healthcare Providers

Abstract: (1) Background: Corporate social responsibility (CSR) is important for every company that cares for sustainable structures. Healthcare providers especially have made social responsibility their goal. However, crises such as the COVID-19 pandemic impacted different activities within the healthcare sector including CSR and its monitoring. However, theory-driven CSR research within the healthcare sector is scarce and monitoring requires a structured understanding of the processes. Therefore, the objective of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 91 publications
0
4
0
1
Order By: Relevance
“…Vale la pena mencionar que el sector financiero y de salud aumentaron sus porcentajes; la literatura empírica soporta esto en términos de ver las crisis como oportunidades para mejorar la reputación corporativa (Fernández-Feijóo Souto, 2009); para el caso del sector salud, dado el impulso económico que recibió de parte del Estado para aumentar la capacidad instalada de camas UCI, se dio la oportunidad para mostrar esfuerzos complementarios para combatir la pandemia. Sin embargo, específicamente las actividades de RSE para otros sectores, al igual que en el resto del mundo, se redujeron (Deselaers et al, 2023).…”
Section: Discussionunclassified
“…Vale la pena mencionar que el sector financiero y de salud aumentaron sus porcentajes; la literatura empírica soporta esto en términos de ver las crisis como oportunidades para mejorar la reputación corporativa (Fernández-Feijóo Souto, 2009); para el caso del sector salud, dado el impulso económico que recibió de parte del Estado para aumentar la capacidad instalada de camas UCI, se dio la oportunidad para mostrar esfuerzos complementarios para combatir la pandemia. Sin embargo, específicamente las actividades de RSE para otros sectores, al igual que en el resto del mundo, se redujeron (Deselaers et al, 2023).…”
Section: Discussionunclassified
“…However, reviewing the current evidence, we can conclude that vaccinations are just one strategy to prevent severe infections and the long-term, post-acute sequelae of infection [ 26 ]. Attempts to overcome post-/long-COVID should take more options than vaccinations into account, such as behavioral interventions and medical rehabilitation treatments addressing the coping mechanisms, and appropriate, safe patient behavior is required [ 13 , 24 , 34 ]. This is especially important because limited workability is problematic not only for the individual (because of limited social participation and economic demands) but also for society (because of limited productivity and skills shortage, and costly reintegration demands to be covered by the social welfare system).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research on life satisfaction found a bidirectional association between clinical and psychological factors, indicating that post-/long-COVID symptoms affect mental well-being but also the other way around, illustrating a vicious circle [ 12 ] in terms of that experiences feed back into setting goals towards adopting and maintaining behaviors [ 13 ]. This is especially important in patients who suffer from post-/long-COVID fatigue, associated with subsequent mental health issues, and if patients do not recover well (e.g., [ 3 , 14 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations